A organização política dos pescadores em uma comunidade ribeirinha no município de Tabatinga/AM - (:unkn) unknown (Universidade Federal do Amazonas, 2007)
The political organization of fishermen configures itself from a series of changes in the fishing industry over the history of the region, the internal dynamics of the communities sobredeterminadas generated by the socio-economic and political environment of the region. From this understanding, the present study is to examine the purpose political organization of fishermen in the community Tauarú in the municipality of Tabatinga / Am. The cut methodology considers the people who participate in studies as important actors in the formulation of new knowledge. The approach of stamp investigative and analytical, characterized as a case study, covering the combination of quantitative and qualitative data collected from the formal and informal representatives of fishermen in the community Tauarú. In this study, adopted is a set of tools and techniques mutually complementary, as application forms, semi-structured, formal and informal conversations, home visits, systematic observation and assistemática, registration fonográfico and photographs. The discussion about the political organization, links to the configuration of social movements in the search for alternatives and strategies for answering the real demands of organized groups. Thus, the study indicates that the fishermen in the Amazon region, began to organize itself in the quest to defend the right to use and management of fish stocks. Therefore, the political organization of fishermen, engendered by changes in the fishery, where despite the difficulties, there is as a strategy to mobilize to have access to fishery resources and property and social services.
Keywords: Movimentos sociais; Organização política; Recursos pesqueiros; Social movements; Political organization; Fish stocks; OUTROS